Produção do probiótico Saccharomyces boulardii em efluente de arroz parboilizado e avaliação da biorremediação - Gaboardi, Giana Carla (2015)
Brazil produced 12.2 million tons of paddy rice in 2013/2014, and the south region was responsible for 60% of the production. The parboiled rice represents 50% of the national rice exports and about 20% of the total rice sold in Brazil. During the parboiling process are generated 2 liters of effluent per kilo of processed grain, generating large volumes of effluent which contains nutrients such as nitrogen and phosphorus, and organic matter. The treatment methodologies used for the treatment of this effluent are aerobic and anaerobic lagoons, activated sludge, chemical precipitation and UASB reactors. Cultivation of yeasts in wastewater has been used as a treatment technique while generating biomass that can be used as probiotic or unicellular protein source. The yeast Saccharomyces boulardii is able to grow in parboiled rice effluent when it is supplemented with extra carbon source. The aim of this study was to evaluate the use of Saccharomyces boulardii on treatment of parboiled rice effluent and biomass production. Trials were carried out for the medium selection to Saccharomyces boulardii cultivation, testing the addition of sucrose or glycerol by-product of biodiesel industry into parboiled rice effluent, collected in a rice processing industry. The best results obtained were on cultivation in effluent supplemented with 1% sucrose, generating 2.4 x 108 CFU.mL-1 of cell viability and phosphorus, nitrogen and COD removal of 72%, 50% and 56%, respectively, after 24 h of culture. After medium selection, the cell growth, yeast biomass production and its influence on the reduction of environmental parameters was analyzed in bioreactor. After 48 h of culture, it was produced 3.8 g L-1 of biomass and 1.8 x 10 11 CFU. L-1. The removal efficiency was 74% for COD and 78% for phosphorus, reaching the phosphorus removal rates required by Conselho Estadual do Meio Ambiente (CONSEMA 128/06). Furthermore, the produced dry yeast biomass and cell viability reached would allow to obtain sufficient probiotics to add to 36 tons of feed for each ton of processed grain. These results show the advantages of Saccharomyces boulardii cultivation in parboiled rice effluent supplemented with sucrose as a treatment system and production of probiotic.